2010
DOI: 10.1111/j.1365-2133.1995.tb16953.x
|View full text |Cite
|
Sign up to set email alerts
|

The Children's Dermatology Life Quality Index (CDLQI): initial validation and practical use

Abstract: Summary Skin disease can cause severe disability and handicap in children. Measurement of the impact of skin disease on the quality of life is required to aid clinical decision‐making, for clinical research, for audit of paediatric dermatology services, and for political reasons, to aid arguments for more resources for the care of children with skin disease. Adult measures are inappropriate, as the lives of children differ markedly from those of adults. The purpose of this study was to create and initially val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
444
2
11

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 835 publications
(475 citation statements)
references
References 10 publications
18
444
2
11
Order By: Relevance
“…Dermatology-specific quality of life was assessed using the IDQoL 41 (for children aged 3 months to < 4 years) and the CDLQI 42 (for children aged 4 years to < 8 years). These instruments have both been validated and are used extensively in dermatology research.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Dermatology-specific quality of life was assessed using the IDQoL 41 (for children aged 3 months to < 4 years) and the CDLQI 42 (for children aged 4 years to < 8 years). These instruments have both been validated and are used extensively in dermatology research.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Patients self-assessed their quality of life using a validated scale specific of their age: the Infant's Dermatitis Quality of Life Index for subjects under 5 years [21], Children's Dermatology Life Quality Index ‘cartoon' for children aged 5-10 [22], the Children's Dermatology Life Quality Index for subjects aged 11-16 [23] and the DLQI for subjects above the age of 16 [11]. …”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of named outcome measure scales for atopic eczema 45 found that, of the 20 named scales in current use, only three have been validated adequately enough to be recommended for use in clinical trials: Severity Scoring of Atopic Dermatitis (SCORAD), 47 Eczema Area and Severity Index (EASI) 48 and the Patient-Oriented Eczema Measure (POEM). 49 Quality-of-life measures specific to dermatology include the Dermatology Quality of Life Index [50][51][52] and Skindex 53,54 Why is a scoping systematic review still needed?…”
Section: Other Recommendations Includedmentioning
confidence: 99%